Prevalence and Tissue Tropism of Edwardsiella spp. in Market-SourcedFinfish in Kano State, Nigeria (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Edwardsiella species are emerging zoonotic pathogens with increasing significance in aquaculture, posing risks to both fish health and public safety. Despite their relevance, data on their distribution in commercially important freshwater fish in Nigeria remain limited. This study investigated the occurrence and tissue distribution of Edwardsiella spp. in two finfish species; Clarias gariepinus (African catfish) and Oreochromis niloticus (Nile tilapia) sourced from Galadima Fish Market, Kano State, Nigeria. A total of 80 organ samples (gills, liver, spleen, and intestine) from 20 live fish specimens were analyzed using standard microbiological and biochemical techniques. The overall isolation rate of Edwardsiella spp. was 5% (2/40) in C. gariepinus and 10% (4/40) in O. niloticus. In C. gariepinus, isolates were found only in the intestine (20%) while in O. niloticus, isolates were detected in the gills (20%), spleen (10%), and intestine (10%), but not in liver tissues of either species. Biochemical tests identified traits consistent with Edwardsiella tarda, including motility, indole production, and hydrogen sulfide generation. Observed prevalence rates were low, suggesting geographical, environmental, or management-related variability. Edwardsiella spp. were present in both fish species, particularly in intestinal and systemic sites, with a higher frequency in O. niloticus. These findings indicate conceivable health threats for consumers and highlight the task played by the fish to serve as reservoirs of zoonotic pathogens. The detection of Edwardsiella spp. in market-sold fish highlights the need for strengthened aquaculture biosecurity, routine diagnostic surveillance, and improved hygienic handling practices to protect consumer health and support sustainable fish farming.